Analysis of the Legal Position of Aceh Qanun in the Indonesian Legal System and Islamic Law Perspective - Muhammadong, Muhammadong (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2026)
Aceh Qanun represents a unique form of regional regulation as it integrates Islamic legal principles into the national legal framework. However, its existence raises critical issues regarding its harmonization with higher laws, including constitutional principles and human rights protections. This study aims to analyze the legal position of Aceh Qanun within the Indonesian legal system and examine its relevance from the perspective of Islamic law. This research employs a qualitative method with a normative approach, utilizing legal document analysis and interviews with legal experts. The findings reveal that formally, Aceh Qanun holds a position equivalent to regional regulations, yet substantively it possesses distinct characteristics due to the incorporation of Islamic legal norms. Its implementation faces significant challenges, particularly potential conflicts with national law in areas such as criminal law, human rights, and gender equality. From an Islamic law perspective, Aceh Qanun does not fully represent comprehensive Sharia principles, as it has undergone contextual adaptation to socio-political realities. Therefore, legal harmonization through continuous dialogue between local and central governments, as well as the broader community, is essential to maintain a balance between local values, Islamic principles, and the national legal system. This study contributes to the discourse on legal pluralism in Indonesia and offers recommendations for strengthening regulatory synchronization in a sustainable manner.